Progressive Multifocal Leukoencephalopathy Risk Mitigation: A Focus on Approved Immunomodulatory Drugs for Multiple Sclerosis Treatment - Hind A. Alnajashi; Foziah Alshamrani (Journal of King Abdulaziz University: Medical Sciences, 2020)
Although treatment options increasingly offer improved efficacy for multiple sclerosis, some have also resulted in an increase in treatment-related risk. Progressive multifocal leukoencephalopathy is an unusual, complex infection typically attacking the central nervous system of an individual with a weakened immune system. Attributed to the infestation of the John Cunningham virus, it has also been found in association with several multiple sclerosis therapies. Progressive multifocal leukoencephalopathy cases have been directly associated with the use of natalizumab, dimethyl fumarate, fingolimod, and ocrelizumab for the treatment of multiple sclerosis. Alemtuzumab and mitoxantrone have been linked to progressive multifocal leukoencephalopathy in treating diseases other than multiple sclerosis, and no progressive multifocal leukoencephalopathy cases have been reported in multiple sclerosis patients. This review will examine progressive multifocal leukoencephalopathy cases associated with multiple sclerosis therapies, strategies to decrease susceptibility to progressive multifocal leukoencephalopathy, and strategies to discontinue higher-risk treatments in favor of lower-risk therapy.